2012
DOI: 10.1063/1.3698286
|View full text |Cite
|
Sign up to set email alerts
|

Shearing radiative collapse with expansion and acceleration

Abstract: We investigate the behaviour of a relativistic spherically symmetric radiative star with an accelerating, expanding and shearing interior matter distribution in the presence of anisotropic pressures. The junction condition can be written in standard form in three cases: linear, Bernoulli and Riccati equations. We can integrate the boundary condition in each case and three classes of new solutions are generated. For particular choices of the metric we investigate the physical properties and consider the limitin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 22 publications
(41 reference statements)
0
40
0
Order By: Relevance
“…This is a necessary condition that ensures continuity of the momentum flux across the boundary of the radiating star. The Santos junction conditions have been generalised to include shear [5,6], the cosmological constant as well as the electromagnetic field [7,8]. Since 1985 there has been a concerted effort in generating exact models of dissipative collapse with Herrera and co-workers establishing many of the fundamental results in terms of stability, energy conditions and thermodynamics of these models [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This is a necessary condition that ensures continuity of the momentum flux across the boundary of the radiating star. The Santos junction conditions have been generalised to include shear [5,6], the cosmological constant as well as the electromagnetic field [7,8]. Since 1985 there has been a concerted effort in generating exact models of dissipative collapse with Herrera and co-workers establishing many of the fundamental results in terms of stability, energy conditions and thermodynamics of these models [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to observe that equation (8) is not equivalent to the original equation (6). The transformation (7), and consequently (8), is not valid for Y ′ = B orẎ = A.…”
Section: Discussionmentioning
confidence: 99%
“…It should be observed that the condition A =Ẏ is a special case of a relationship derived by Thirrukanesh et al [6] in their investigation of a radiating star. To solve (10) we follow their approach and assume Y is a separable function of the form…”
Section: B Category 2: a =ẏmentioning
confidence: 99%
See 2 more Smart Citations